Bridging the Digital Divide: An empirical analysis of public programs to increase broadband adoption. (February 2022) - Randolph Beard, T.; Ford, George S.; Stern, Michael
Highlights: America spends billions to close the Digital Divide, but adoption disparities persist. We quantify the effect of programs established by the American Reinvestment and Recovery Act of 2009 . We find no positive effect on home broadband adoption from these programs. Abstract: The COVID pandemic has rekindled the strong interest in broadband adoption, with the U.S. Congress recently setting aside 65 billion to shrink the availability and adoption gaps. But America has spent billions trying to close the Digital Divide in the past, yet adoption disparities along many dimensions persist. In this article, we offer an empirical analysis of past broadband adoption programs by quantifying the effect of several programs established by the American Reinvestment and Recovery Act of 2009 . Applying a Difference-in-Differences model to Census data on adoption, we find no positive effect on home broadband adoption from programs funded by the Broadband Technology Opportunity Program ("BTOP").